Investing in resilience: Climate risks and opportunities in Ethiopia's Key agricultural value chains. Investor brief for policymakers - ImpactSF; Tetratech; Centro Agronómico Tropical de Investigación y Enseñanza (CATIE); Mercy Corps Agrifin; Ethiopian Agricultural Tranformation Agency (ATI); Ministry of Agriculture; Bioversity International and International Center of Tropical Agriculture; Gates Foundation (2025)
This investor brief is the third in a series summarizing action points from the Clim-ARM investment blueprint reports (see below) for different stakeholders. This brief is intended for policymakers to highlight investment opportunities in Ethiopian agriculture that aims to address climate risks while building resilient value chains. These investment opportunities are described in more detail in the Clim-ARM project report where eight critical value chains are assessed. 1. Clim-ARM project investment blueprint report: hdl.handle.net/10568/173562 2. A summary of the project investment blueprint report: hdl.handle.net/10568/177044 3. Investor brief for concessional providers: hdl.handle.net/10568/177046 4. Investor brief for commercial capital providers: hdl.handle.net/10568/177045